A Simplified Palaeoceanography Archiving System (PARIS) and GUI for Storage and Visualisation of Marine Sediment Core Proxy Data vs Age and Depth. (20th May 2022) - Lougheed, Bryan C.; Waelbroeck, Claire; Smialkowski, Nicolas; Riveiros, Natalia Vazquez; Obrochta, Stephen P.
Scientific discovery can be aided when data are shared following the principles of findability, accessibility, interoperability, reusability (FAIR) data (Wilkinson et al., 2016 ). Recent discussions in the palaeoclimate literature have focussed on defining the ideal database format for storing data and associated metadata. Here, we highlight an often overlooked primary process in widespread adoption of FAIR data, namely the systematic creation of machine readable data at source (i.e. at the field and laboratory level). We detail a file naming and structuring method that was used at LSCE to store data in text file format in a way that is machine-readable, and also human-friendly to persons of all levels of computer proficiency, thus encouraging the adoption of a machine-readable ethos at the very start of a project. Thanks to the relative simplicity of downcore palaeoclimate data, we demonstrate the power of this simple but powerful file format to function as a basic database in itself: we provide a Matlab-based GUI tool that allows users to search and visualise isotope data by sediment core location and species type, against either depth or age. We share the database format here so that other laboratories might consider developing a similar approach depending on their own needs and requirements.